Analisis Komparasi Kinerja Keuangan Daerah Sebelum Covid-19 dan Semasa Covid-19 di Kabupaten Kotawaringin Timur Tahun 2018-2021 - Josia Ananta; Alexandra Hukom (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The purpose of this study is to evaluate and compare the financial performance of district local governments in East Kotawaringin before and after the Covid-19 pandemic. The study's population consists of financial data from the regional administration of East Kotawaringin Regency, which is located in the province of Central Kalimantan. This study is a descriptive quantitative investigation. Using SPSS software, the study team performed a Paired T-test analysis to acquire results for homogeneity, normality, and one-way Anova tests. The documentation approach is employed in the sample procedure. Method This study use quantitative descriptive analysis for its analysis. The secondary data used in this study came from books, supporting journals, the internet, and the APBD posture in East Kowaringin Regency between 2018 and 2021.